2015
DOI: 10.17219/acem/29223
|View full text |Cite
|
Sign up to set email alerts
|

An Assay of Selected Serum Amino Acids in Patients with Type 2 Diabetes Mellitus

Abstract: Background. Amino acids are the building blocks of proteins. In case of insulin resistance, which is typical for type 2 diabetes mellitus (T2DM), proteolysis is increased and protein synthesis is decreased; therefore, we can observe changes in the levels of amino acids in diabetics vs. non-diabetics. Objectives. The aim of this study was to find differences in the levels of selected amino acids between patients with diabetes (type 2) and a control group. Material and Methods. Amino acids were derivatized with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 14 publications
(15 reference statements)
3
29
1
Order By: Relevance
“…We found significant differences in AAA and BCAA concentrations between women and men, but not between the patients and the control group. This method was also used for the determination of serum amino acids in patients with type 2 diabetes mellitus [15]. The serum levels of BCAA were statistically significantly increased in patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found significant differences in AAA and BCAA concentrations between women and men, but not between the patients and the control group. This method was also used for the determination of serum amino acids in patients with type 2 diabetes mellitus [15]. The serum levels of BCAA were statistically significantly increased in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients with diabetes mellitus were excluded from the study. Insulin resistance results in increased proteolysis and BCAA levels are elevated [15,22]. In skeletal muscle, BCAAs act as an essential donor of nitrogen in the BCAA transaminase reaction to form glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…12,15 Previous studies indicated that plasma glycine level is a negative biomarker in patients with diabetes mellitus. [18][19][20][21] Glycine metabolism pathway indicates the participation of many other important metabolites that mostly serve in the biosynthesis of glycine. However, many of these metabolites have not been proven to be associated with insulin resistance or diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…A study of children with type 1 diabetes and non‐diabetic controls found that the concentration of L‐serine in plasma was decreased by 42% in patients . Similar studies of patients with type 2 diabetes have found reduced L‐serine concentration in blood . The postprandial L‐serine concentration in response to a standardized meal differs between type 2 diabetes patients and non‐diabetic controls, with patients having a reduced concentration of L‐serine in blood, while controls have an increased concentration .…”
mentioning
confidence: 95%